Empowerment and Reflexivity Vector of Self-Determination, Self-esteem, and Knowledge of one’s Own Learning Style and Technological Strategy: Case of the Digital Personal Project - Bassiri, Mustapha; Abderrazzak, M.; Belaaouad, S.; Jammoukh, M.; Mansouri, K. (TECCIENCIA, 2022)
AAD Self-Digested Learning is a learning strategy oriented towards the actor subject, capable of reconfiguring one's resources autonomously and responsibly. The latter makes it possible to conceive one's personal and collective action project in a conscious and resonated way. ADA offers adult learners the opportunity to plan and manage their resources, collaborate with their peers to develop cultural, methodological and technological competences. Nevertheless, the implementation of an AAD-centric approach depends on andragogic and pedagogical expertise, by managing the complexity of the teaching-learning situation from the modeling and personalization of a family of learning situation differentiated and personalized to the needs and learning styles of adult learners. At the same time, current andragogic trends continue to proclaim the use of a learning approach to reflexivity and self-management of personal and collective action projects. Identifying the family of self-management problem situations can help learners acquire these skills. However, most academic training schemes favor expository and masterful approaches to the detriment of andragogic approaches, soliciting the power of analysis, reflection and management of their own learning processes. The main objective of this study is to show the importance of self-regulated learning and its close relationship with the planning and management of reflective learning. We propose a systemic and holistic modeling of pedagogical strategies, promoting the self-management of learning. The diversification of teaching strategies and knowledge of andragogic principles constitute the guideline, which guide and help learners to understand the process of construction and self-regulation of updated personal action projects (AHS). The identification of the family of self-management situation of learning (SAA), founds the new device of didactic engineering of tasks (according to an ergonomic aim and professional didactics).